Review articleAutoimmune reactions in the course of the hepatitis C virus (HCV) infection - Tomasiewicz, Krzysztof; Pokora-Pachowicz, Agnieszka; Kiciak, Sławomir (Clinical and Experimental Hepatology, 2015)
The immune response to the presence of the virus, both specific and non-specific, plays a decisive role in the natural history of the infection, and influences the intensity of lesions in the liver. Despite the great progress which we were able to observe over the last several years, many issues still require clarification. The problem of autoimmune reactions during hepatitis C virus (HCV) infection includes at least two issues. First, the risk of exacerbating reactions against the organism’s own tissues that existed before the treatment. There is also an increased risk of the development of de novo autoimmune reactions, triggered mostly by interferon α. Hepatitis C virus infection predisposes to the development of diseases characterised as being certainly or probably immune-mediated. Currently the situation has changed due to introducing non-interferon therapies for HCV treatment, which eliminate the risk associated with immunotherapy in patients with autoimmune diseases, yet the therapies are not widely available.